Clinical advances in racemic epinephrine for pediatric croup: a mini-review of evidence and practice - Yu-tong Hou; Qi Shi; Lin Zhang; Qian Cheng (Frontiers in Pediatrics)
This mini-review critically evaluates the contemporary evidence regarding racemic epinephrine's role in pediatric croup management. As the pharmacological mainstay for acute airway obstruction, racemic epinephrine demonstrates rapid efficacy through dual α₁-adrenergic vasoconstriction and β2-mediated bronchodilation, achieving clinically significant Westley Croup Score reductions (2–3 points) within 30 min of administration. Current evidence establishes therapeutic equipoise between racemic and L-epinephrine formulations, though important disparities exist in global accessibility and cost-effectiveness. The transient therapeutic window (90–120 min) necessitates careful monitoring and underscores the importance of concomitant corticosteroid administration for sustained symptom control. While the safety profile remains favorable, with transient cardiovascular effects representing the primary concern, several evidence gaps persist regarding optimal retreatment intervals, viral subtype-specific responses, and long-term neurodevelopmental outcomes. Emerging research directions highlight the potential of advanced delivery systems and biomarker-guided approaches to optimize therapy. These findings collectively reinforce racemic epinephrine's position as an essential bridging intervention during the critical latency period preceding corticosteroid efficacy, while emphasizing the need for standardized protocols to ensure optimal clinical implementation across diverse healthcare settings.